2021
DOI: 10.1371/journal.pone.0243924
|View full text |Cite
|
Sign up to set email alerts
|

Protective factors against tobacco and alcohol use among pregnant women from a tribal nation in the Central United States

Abstract: Identifying social determinants of tobacco and alcohol use during pregnancy is critical to improving health outcomes for the next generation. This is especially important on a rural Tribal Nation where influences such as isolation, cultural barriers, and historical trauma have made it uniquely challenging to prevent substance use during pregnancy. The purpose of this study is to identify population-specific factors that are protective against smoking and drinking during pregnancy. We used data from 421 pregnan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The authors concluded their findings “challenge commonly held beliefs of elevated alcohol consumption among AIAN compared with other races.” 17 Education, employment, and mental health were all protective against drinking before and during pregnancy in AIAN women. 49,50 One national study composed of respondents representing diverse races and ethnicities reported that the risk for alcohol-exposed pregnancy did not differ by race and ethnicity but was positively associated with level of education. 42…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors concluded their findings “challenge commonly held beliefs of elevated alcohol consumption among AIAN compared with other races.” 17 Education, employment, and mental health were all protective against drinking before and during pregnancy in AIAN women. 49,50 One national study composed of respondents representing diverse races and ethnicities reported that the risk for alcohol-exposed pregnancy did not differ by race and ethnicity but was positively associated with level of education. 42…”
Section: Resultsmentioning
confidence: 99%
“…17 Education, employment, and mental health were all protective against drinking before and during pregnancy in AIAN women. 49,50 One national study composed of respondents representing diverse races and ethnicities reported that the risk for alcohol-exposed pregnancy did not differ by race and ethnicity but was positively associated with level of education. 42 In addition, risky drinking prior to pregnancy has been found to influence continued drinking during pregnancy.…”
Section: Sampling In Geographic Regionsmentioning
confidence: 99%
“…Racial differences are observed in substance use during pregnancy and reproductive-potential years. For example, substance use rates are higher in Indigenous pregnant women than the national average, with smoking rates as high as 75% 22 . American Indian or Alaska Native women have the highest risk of death from a prescription opioid overdose 23…”
Section: Racial Differences In the Presentation Of Perinatal Psychiat...mentioning
confidence: 99%